On the stable difference scheme for the time delay telegraph equation - Ashyralyev, A.; Turk, K.; Agirseven, D. (KSU Publ., 2020)
The stable difference scheme for the approximate solution of the initial boundary value problem for the telegraph equation with time delay in a Hilbert space is presented. The main theorem on stability of the difference scheme is established. In applications, stability estimates for the solution of difference schemes for the two type of the time delay telegraph equations are obtained. As a test problem, one-dimensional delay telegraph equation with nonlocal boundary conditions is considered. Numerical results are provided
Кідіртпелі телеграф теңдеуі үшін орнықты айырымдық схемасы туралы
Об устойчивой разностной схеме для уравнения телеграфа с задержкой
Keywords: difference schemes; delay telegraph equations; stability